2013
DOI: 10.3109/14767058.2013.849240
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin D deficiency in Egyptian mothers and their neonates and possible related factors

Abstract: Maternal vitamin D levels strongly correlate with neonatal levels. Maternal vitamin D deficiency is a real problem in Egypt; this is generally related to high BMI, low fish consumption, low educational level, and limited skin exposure.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
24
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 39 publications
(37 citation statements)
references
References 28 publications
4
24
1
Order By: Relevance
“…A study by El Rifai et al of 135 pregnant Egyptian women at ≥37 weeks’ gestation (immediately before delivery) reported vitamin D insufficiency (serum 25(OH)D < 50 nmol/L) and inadequacy (serum 25(OH)D 50–80 nmol/L) in 40% and 28.9% of patients, respectively [26]. In another study, 54% of 50 pregnant women and 72.6% of 51 lactating women were found to have insufficient vitamin D (serum 25(OH)D < 50 nmol/L) [27].…”
Section: Prevalence Of Micronutrient Deficiencies In the Middle Eastmentioning
confidence: 99%
See 4 more Smart Citations
“…A study by El Rifai et al of 135 pregnant Egyptian women at ≥37 weeks’ gestation (immediately before delivery) reported vitamin D insufficiency (serum 25(OH)D < 50 nmol/L) and inadequacy (serum 25(OH)D 50–80 nmol/L) in 40% and 28.9% of patients, respectively [26]. In another study, 54% of 50 pregnant women and 72.6% of 51 lactating women were found to have insufficient vitamin D (serum 25(OH)D < 50 nmol/L) [27].…”
Section: Prevalence Of Micronutrient Deficiencies In the Middle Eastmentioning
confidence: 99%
“…In another study, 54% of 50 pregnant women and 72.6% of 51 lactating women were found to have insufficient vitamin D (serum 25(OH)D < 50 nmol/L) [27]. Neonatal serum 25(OH)D was consistently found to correlate with maternal serum status in studies reported from Egypt and the KSA [25,26,28]. …”
Section: Prevalence Of Micronutrient Deficiencies In the Middle Eastmentioning
confidence: 99%
See 3 more Smart Citations